Analiza vzorcev vedenj, povezanih z zdravjem - Majerič, Matej (Šport (Ljubljana), 2016)
The aim of research was to study the nutrition habits, physical activity, alcohol and tobacco consumption, mental health, and motives for lifestyle change among students. The empirical research was carried on the sample of 171 undergraduate and master students at Faculty of Social Sciences, University of Ljubljana. The collected data with semi-structured questionnaire included studentsć self-evaluation of their lifestyle across different areas. Data analysis was made with SPSS, based on bivariate statistics analysis. Respondents' health and care for them were self-evaluated as very good (Mean=4.84). Daily vegetable consumption (Mean=4.19), fruit consumption (Mean=4.02), and regular physical activity, at least 30 minutes per day, mostly in non-organised forms (Mean=3.03), described the lifestyle of students. The data shows us the comparability of similar studies that have been carried out in Slovenia. The conclusions are useful for narrower and wider professional public.
Keywords: alcohol consumption; gibalne navade; hierarchical cluster analysis; lifestyle changes; nutrition habits; physical activity; prehranske navade; sport; spremembe življenskega sloga; student health; šport; študenti; tobacco consumption; ukvarjanje s športom; Univerza v Ljubljani; uživanje alkohola; uživanje tobaka; zdravje študentov